Catellatospora tritici sp. nov., a novel cellulase-producing actinobacterium isolated from rhizosphere soil of wheat (Triticum aestivum L.) and emended description of the genus Catellatospora. Issue 6 (9th June 2022) - Yang, Yanming; Qian, Lulu; Lin, Jiaying; Qi, Cuiping; Zhao, Tianxin; Wang, Xiangjing; Zhao, Junwei; Xiang, Wensheng
Abstract : A Gram-positive, cellulose-degrading actinobacterium, designed strain NEAU-YM18 T, was isolated from rhizosphere soil of wheat ( Triticum aestivum L.) sampled in Langfang, Hebei Province, PR China. The novel strain was characterized using a polyphasic approach. Morphological and chemotaxonomic characteristics confirmed that strain NEAU-YM18 T belonged to the genus Catellatospora . Cells of strain NEAU-YM18 T were observed to contain meso - and 3-hydroxy-diaminopimelic acids as diagnostic cell-wall amino acids. The acyl type of the cell-wall muramic acid was glycolyl. The whole-cell hydrolysates were xylose, glucose and ribose. The phospholipids consisted of diphosphatidylglycerol, phosphatidylethanolamine and phosphatidylinositol. The major fatty acids were iso-C15 : 0, iso-C16 : 0, C18 : 1  ω 9 c and summed feature 5 (anteiso-C18 : 0 /C18 : 2  ω 6, 9 c ). The menaquinones were MK-9(H4 ), MK-9(H6 ) and MK-9(H2 ). The DNA G+C content was 71.1 %. The results of 16S rRNA gene sequence and phylogenetic analyses indicated that strain NEAU-YM18 T was closely related to Catellatospora chokoriensis 2-25(1) T (98.4 % 16S rRNA gene sequence similarity), Catellatospora vulcania NEAU-JM1 T (98.3%) and Catellatospora sichuanensis H14505 T (98.3 %) and formed a branch with C. sichuanensis H14505 T . Furthermore, the whole genome phylogeny of strain NEAU-YM18 T showed that the strain formed an independent clade. The digital DNA–DNA hybridization results between NEAU-YM18 T and C. chokoriensis 2-25(1) T, C. vulcania NEAU-JM1 T and C. sichuanensis H14505 T were 25.0, 24.7 and 24.7 %, respectively, and the whole-genome average nucleotide identity values between them were 81.5, 81.4 and 81.4 %, respectively. These genetic results and some phenotypic characteristics could distinguish strain NEAU-YM18 T from its reference strains. In addition, genomic analysis confirmed that strain NEAU-YM18 T had the potential to decompose cellulose and produce bioactive compounds. Therefore, strain NEAU-YM18 T represents a novel species of the genus Catellatospora, for which the name Catellatospora tritici sp. nov. is proposed. The type strain is NEAU-YM18 T (=CCTCC AA 2020040 T =JCM 33977 T ).